Censorship of Kurdish Identity in Northern Kurdistan From the Archives of the Turkish Republic 1923-1945 - Injagha, Dr. Saman Mustafa Rashid (Sulaimani Journal for Humanities, 2025)
The new Republic of Turkey was established in 1923 on the remains of the multicultural, multi-ethnic, multilingual, and multinational Ottoman Empire. This new state did not acknowledge the distinct identities of its constituent ethnic groups including Kurds, Armenians, and Circassians. Instead, it established Turkish ethnicity, identity, and language as the sole identity of the state, creating a melting pot and attempting to assimilate all other distinct identities into the Turkish identity. We have numerous Turkish Republic documents at our disposal that are specifically related to decisions to censor Kurdish identity (language, history, and Kurdish literature) in the new Turkish Republic. Therefore, this research aims to investigate the issue of censorship and prohibition of Kurdish identity during the specified period in that country, in light of Turkish Republic documents, constitution, and laws. The research adopts a historical research methodology for writing its sections. The research is divided into two main chapters: the first chapter discusses the censorship of Kurdish identity in Northern Kurdistan from 1923-1938, and the second chapter covers the censorship of Kurdish identity in Northern Kurdistan from 1938-1945.
Keywords: Turkish Republic; Kemalists; Single Identity; Kurdish Identity; Censorship and Prohibition